Tile Artist Naciye Avlupınar and Her Artistic Activities in The Context of Living Human Treasures / Yaşayan İnsan Hazineleri Bağlamında Çini Sanatçısı Naciye Nur Avlupınar ve Sanatsal Faaliyetleri - Münire Baysan (Folklor/Edebiyat, 2021)
It is extremely important to preserve the culture that constitutes the character and identity of societies, and to be able to pass it on to future generations in an original and contemporary way. Traditional handicrafts comprise an important part of culture. Tile art, which is among the intangible cultural values, is one of these arts. Tile, which came to the Anatolian lands with the Seljuks and was named as kâşî and evânî in the past, is an ancient Turkish art. It is thanks to the artists who have carried it to the present day remaining faithful to the original that the tile art has been able to survive over centuries without breaking off its traditional roots. The subject of this article is the art of Naciye Nur Avlupınar, the exemplary character of woman’s works in tile art, and her artistic activities in the context of the Living Human Treasure. The artist, who has been dealing with tile art for thirty-six years, has grown up with the master-apprentice tradition. She brought many different innovations to her art by adhering to the original, exemplified these innovations in her own works, introduced the Turkish tile art with its 21st century features with exhibitions held in and outside the country, and raised many students in this field. This study aims to evaluate the innovations, works and artistic style of Avlupınar, who has a grasp of both the art and craft part of this work, as well as women who work only as workers, painters and engraving masters in the tile industry on a piece work basis. In the theoretical part of this study, the literature review and in the data collection part an in-depth interview was conducted using the interview method.